Clinical Insights and Diagnostic Dilemmas: Two Cases of Livedoid Vasculitis - Earlia, Nanda; Budini, Sulamsih Sri; Lestari, Wahyu; Handriani, Risna; Ismida, Fitri Dewi; Pradistha, Aldilla; Dinillah, Teuku Muhammad Muizzy; Vemulen, Dara Avinda; Athira, Athira (Indonesian Journal of Case Reports, 2024)
Livedoid Vasculitis (LV) is a thrombo-occlusive vasculopathy involving dermal vessels, especially in the lower extremities. Clinical symptoms of LV are chronic, recurrent, scarring, and painful purpuric ulcers. Diagnosing and providing therapy for LV is a challenge because there are no standard guidelines. We present clinical insights and diagnostic approaches on two cases of LV to improve early diagnosis and prevent misdiagnosis, which were confirmed based on history, dermatological examination, and skin biopsy. In the first case, it was a woman, 23 years old, who came with complaints of a blackish-red rash appearing on both legs. There were scars on several parts of the patient's legs, which felt painful, and the legs looked swollen. On histopathological examination, fibrin deposition in the vessel walls, endothelial proliferation, and intraluminal hyaline thrombin were found. In the second case, it was a man, 19 years old, who came with complaints of pain when walking accompanied by wounds on both lower legs. On histopathological examination, fibrin deposition in the vessel walls, endothelial proliferation, and intraluminal hyaline thrombin were found. The conclusion from the histopathology results was LV. After receiving therapy, both cases showed improvement: swelling in the legs was reduced, red and black rashes began to disappear, ulcers improved, pain decreased, and scars became blurred. These two cases provide examples of success in diagnosing LV. Being able to diagnose LV early and correctly is very important so that adequate therapy can be given and good outcomes can be achieved.